Mitochondrial DNA haplogroups and risk of attention deficit and hyperactivity disorder in European Americans - Chang, Xiao (Transl Psychiatry, 2020)
Although mitochondrial dysfunction has been implicated in the pathophysiology of attention deficit and hyperactivity disorder ADHD, the role of mitochondrial DNA (mtDNA) has not been extensively investigated. To determine whether mtDNA haplogroups influence risk of ADHD, we performed a case-control study comprising 2076 ADHD cases and 5078 healthy controls, all of whom were European decedents recruited from The Children’s Hospital of Philadelphia (CHOP). Associations between eight major European mtDNA Haplogroups and ADHD risk were assessed in three independent European cohorts. Meta-analysis of the three studies indicated that mtDNA haplogroups K (odds ratio = 0.69, P = 2.24 × 10(−4), P(corrected) = 1.79 × 10(−3)) and U (odds ratio = 0.77, P = 8.88 × 10(−4), P(corrected) = 7.11 × 10(−3)) were significantly associated with reduced risk of ADHD. In contrast, haplogroup HHV* (odds ratio = 1.18, P = 2.32 × 10(−3), P(corrected) = 0.019) was significantly associated with increased risk of ADHD. Our results provide novel insight into the genetic basis of ADHD, implicating mitochondrial mechanisms in the pathophysiology of this relatively common psychiatric disorder.